Vitamin D Supplementation for Children with Epilepsy on Antiseizure Medications: A Randomized Controlled Trial - Fahad A. Bashiri; Abrar Hudairi; Muddathir H. Hamad; Lujain K. Al-Sulimani; Doua Al Homyani; Dimah Al Saqabi; Amal Y. Kentab; Reem A. Al Khalifah (MDPI AG, 2024)
Background: Antiseizure medications (ASMs) are crucial for managing epilepsy in children. However, a well-documented side effect of ASMs is their impact on bone health, often due to interference with vitamin D metabolism. This can lead to vitamin D deficiency in children with epilepsy. This study aimed to determine if a daily dose of 400 IU or 1000 IU would maintain adequate vitamin D levels in children with epilepsy. Methods: A phase IV randomized controlled trial enrolled children aged 2-16 years with epilepsy and receiving antiseizure medications. Children were divided into two groups: the monotherapy group, which was defined as children on one antiseizure medication (ASM), and the polytherapy group, which was defined as children receiving two or more ASMs. Eligible children with levels above 75 nmol/L were randomized to receive a maintenance dose of either 400 IU/day or 1000 IU/day of cholecalciferol. Baseline and 6-month assessments included demographic data, anthropometric measurements, seizure type, medications, seizure control, and 25(OH)D level. Results: Out of 163 children, 90 were on monotherapy and 25 on polytherapy. After 6 months of vitamin D maintenance, the proportion of children with 25(OH)D concentration below 75 nmol/L was 75.0% in the 400 IU group and 54.8% in the 1000 IU group. In the monotherapy group, baseline seizure-free children increased from 69% to 83.6% after treating vitamin D deficiency. Conclusion: Daily vitamin D supplementation with 1000 IU may be beneficial for children with epilepsy, particularly those receiving monotherapy, to maintain sufficiency and potentially improve seizure control.